Electronic cigarettes for smoking cessation - Hartmann-Boyce, J; Begh, R; Aveyard, P (BMJ Publishing Group, 2018)
- Electronic cigarettes (e-cigarettes) were originally designed as a smoking cessation aid, and the limited evidence available suggests e-cigarettes containing nicotine may help people stop smoking. - Evidence suggests e-cigarettes are considerably safer than traditional cigarettes. - The technology used in e-cigarettes has evolved considerably over time, and newer devices are typically better at delivering nicotine, which might enhance effectiveness.